A Central Sterile Processing and Hospital Epidemiology and Infection Control Collaboration to Ensure Safe Patient Care. (29th June 2020) - Nack, Brenda; Nowakowski, Elaine; Nicholson, Frances
ABSTRACT: Cleaning, disinfection, and sterilization (CDS) practices and protocols are the cornerstone of infection control and patient safety. Central sterile processing (CSP) leaders are responsible for updating policies and procedures for sterile processing and ensuring CSP staff members process instruments correctly. Monitoring staff member practices can be a demanding and difficult task, but it is critical for safe patient outcomes. The CSP and perioperative leaders at our facility found that regular consultation and collaboration with the Department of Hospital Epidemiology and Infection Control (HEIC) is an effective way to ensure that patient safety is at the forefront of CDS practices. These leaders established an oversight committee to address a variety of infection prevention concerns, including environment of care rounds, implementation of manufacturers' instructions for use, and CDS standardization. This article highlights how CSP and HEIC leaders and staff members partnered to implement and sustain CDS best practices and protocols.